Beyond the cybernetic loop: smart” pain technology in a recursive society - Benjamin Lipp; Stephen Hilgartner (Big Data & Society)
This article examines emerging “smart” pain technologies in the United States. New wearable and implantable devices aim to partly remove human decision-making from pain management, delegating it to more or less closed feedback loops that capture signals directly from the body, process them algorithmically, and administer electrical stimulation to modulate nerve response. This endeavor to create increasingly “closed loop” pain treatment reflects both the cybernetic dream of building self-regulating machines and biomedicine's discontent with the subjectivity of pain. The article conceptualizes and empirically explores the building and maintaining of loops in pain management, examining this sociotechnical process and the many elements it implicates, both within and beyond pain management. We focus on two specific devices: one implantable and the other wearable. The analysis shows how physicians and company officials imagine—and actively seek to realize—changes in the role of patients, the nature of medical expertise, the understanding of chronic pain, and the business models of companies. We argue that such activities are a type of technoscientific activity that portends potentially new forms of healthcare and social life. Finally, we propose that an analysis of “looping techniques” can contribute to recently advanced theories of a recursive society by demonstrating how building and maintaining loops shift different actors in and out, interface them at different scales, and establish new regimes of control.